Transformation from Blended to Online Learning: A Four-Year Longitudinal Cross-Sectional Interprofessional Study - Kari Almendingen; Torhild Skotheim; Ellen Merethe Magnus (MDPI AG, 2023)
Professional students need to train in online interprofessional collaboration (IPC). During a longitudinal evaluation for 2018-2022 of an interprofessional learning (IPL) curriculum, nearly 7000 students from health, social care, and teacher education programs completed indicator questions concerning learning about child-related topics and skills required for IPC during their first, second, and third curriculum years of study. The students worked in student-led IPL groups according to a case-based learning approach. Online IPL yielded lower mean scores than in-person IPL. The decreased learning outcomes from year 2 to year 3 for the IPL initiative are not due to the online delivery mode. The lack of reported progress in the IPL courses is more likely due to students not experiencing a gain in IPL learning outcomes. Significant differences were found between teacher education and child welfare students and health and social care students, reflecting IPC challenges in working life. We conclude that online IPL is forward-looking because candidates must be prepared for online IPC and for helping users, such as children, online. Although our data support that IPL is complex, the learning experience has tremendous transfer value to welfare services because we assume that the same issues will appear in IPC.